Artificial Intelligence As A Legal Subject: An Existentialist Philosophy Perspective - Halim, Chandera; Putri, Koleta Donna Indhayana (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The increasing complexity of artificial intelligence (AI) has sparked debates regarding its legal status, particularly whether AI can be considered a legal subject. This study examines the issue through the lens of existentialist philosophy, which emphasizes freedom, consciousness, and responsibility as fundamental aspects of existence. A qualitative approach is employed, utilizing philosophical analysis of subjectivity and existence based on the thoughts of existentialist figures such as Jean-Paul Sartre and Martin Heidegger. The findings reveal that although AI can act autonomously and mimic human decision-making, it lacks self-awareness and existential freedom. Consequently, from an existentialist perspective, AI does not qualify as a legal subject, as it does not possess authentic existence and moral responsibility. This conclusion underscores that AI's legal status is more appropriately categorized as a legal object with specific regulations rather than an entity with legal rights and obligations